Understanding Knife Crime and Trust in Police with Young People in East London - Skarlatidou, Artemis (Crime & delinquency, 2023)
We explore young people?s experiences and perceptions of knife crime, and we compare these to the understanding of police experts, to explore the perceptions shaping trust in the police and policing. We carry out an experience sampling survey deployed using a mobile application reflecting on safety and knife crime, to understand young people?s daily lived experiences. We then use the mental models approach to interview young people and police experts and construct a shared mental model which identifies mismatches between the two groups and key areas of discord related to breakdown of trust and communication. We identify gaps, misconceptions and expectations for re-establishing trust and propose strategies to tackle knife crime and improve trust between young people and the police.